A Socioecological Perspective Regarding Risk Factors for Driving Under the Influence of Marijuana Among Young Adults - Carla J Berg (SAGE Publishing, 2018)
Young adults are at high risk for using marijuana, driving under the influence (DUI) of marijuana, and fatalities or serious injuries from motor vehicle crashes related to DUI of marijuana. Within the context of increased legalization of marijuana use and shifting social norms, these public health concerns are particularly prominent. Drawing from a socioecological perspective, this commentary summarizes the literature indicating the importance of multilevel influences on DUI of marijuana among young adults. Indeed, prior research has indicated that risk for DUI of marijuana is associated with policy-level factors such as state and local policies related to marijuana, community-level factors including marijuana access (eg, legalized retail, black market), interpersonal influences including social norms, and intrapersonal factors such as risk perceptions of marijuana use and DUI. This literature should inform future research and practice aiming to develop, test, and implement multilevel interventions and develop messaging strategies aimed at curtailing DUI of marijuana.